A new transformation of aminopyridines upon diazotization in acetonitrile with the formation of N-pyridinylacetamides; Russian Chemical Bulletin; Vol. 65, iss. 9 - Chudinov A. A. Aleksey Andreevich; Dovbnya R. S. Rada Sergeevna; Krasnokutskaya E. A . Elena Aleksandrovna; Ogorodnikov V. D. Vladimir Danilovich; Filimonova I. L. Irina Leonidovna (2016, 2016)
Title screen